1982
DOI: 10.1111/j.1365-2842.1982.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in recurrent headache and mandibular dysfunction after treatment with new complete dentures

Abstract: The changes in headache and mandibular dysfunction were studied in a group of forty-three complete denture wearers 6 months after treatment with new complete dentures. All patients completed a questionnaire and all were subjected to clinical examination of the function of the masticatory system. Eleven of the seventeen patients with recurrent headache reported less frequent headache 6 months after treatment and nine reported that the headache was less severe. There was also a statistically significant reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…The great individual variation in functional adaptation among denture wearers has been shown previously (Bergman & Carlsson, 1972;Magnusson, 1982;Laine, 1982).…”
Section: Discussionmentioning
confidence: 87%
“…The great individual variation in functional adaptation among denture wearers has been shown previously (Bergman & Carlsson, 1972;Magnusson, 1982;Laine, 1982).…”
Section: Discussionmentioning
confidence: 87%
“…It is also interesting that interocclusal appliances which always increase the vertical dimension are successfully used to treat craniomandibular disorders, and that thicker interocclusal appliances provide better and faster relief (Manns et al, 1983). No association exists between a decrease in OVD and craniomandibular disorders (Magnusson, 1982;Wilding and Owen, 1987 (Christensen, 1970;Carlsson et al, 1979). These symptoms last only a few days, even when the increase is larger than the free-way space itself (Carlsson et al, 1979;Kohno and Bando, 1983;Gross and Ormianer, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Repeating these measurements two or three times does not increase precision (Cohen, 1957). Given this wide variability, the clinical relevance of the PVD may be challenged, and many clinicians have proposed determination of the OVD as the primary clinical objective (Nairn, 1976 (Magnusson, 1982;Dahl and Krogstad, 1985) have shown that there is no proof of a link between alteration in OVD and the occurrence of temporomandibular disorder. I The change may be due to loss of teeth (Atwood, 1956), tooth wear (Tallgren, 1957), prosthetic treatment (Swerdlow, 1964;Gross and Ormianer, 1994), or the reduction in alveolar height that occurs in the wearer of complete dentures (Tallgren, 1972;Tallgren and Solow, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…To the author's knowledge, the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) have not been used to assess the prevalence of this condition among complete denture patients yet. This tool has advantages over older TMD assessment tools used in other studies. In addition, identification of prosthetic factors associated with TMD would provide a better understanding about its aetiology and be useful in the management of this complex condition.…”
Section: Introductionmentioning
confidence: 99%